Comprehensive assessment of inflammatory, epigenetic, and cardioimaging biomarkers in the progressive course of coronary heart disease (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. In this study, the prognostic significance of a multibiomarker model, including epigenetic markers (miR-155), inflammatory cytokines (TNF-α, IL-1β) and noninvasive cardiovisualizing patterns, was evaluated for assessing the risk of progressive coronary heart disease (CHD). Materials and methods. A comprehensive assessment of correlations between the parameters of coronary atherosclerosis according to contrast MSCT angiography (coronary calcium index, degree of stenosis, remodeling index, index of involvement-SIS, density, volume and mass of plaques) and biomarker levels was carried out in 152 patients with stable and unstable forms of coronary artery disease. miR-155 expression was determined by real-time polymerase chain reaction on a Rotor–Gene Q device, and concentrations of proinflammatory cytokines were determined by enzyme immunoassay. Results. A comprehensive assessment of correlations between the parameters of coronary atherosclerosis according to contrast MSCT angiography (coronary calcium index, degree of stenosis, remodeling index, index of involvement-SIS, density, volume and mass of plaques) and biomarker levels was carried out in 152 patients with stable and unstable forms of coronary artery disease. miR-155 expression was determined by real-time polymerase chain reaction on a Rotor–Gene Q device, and concentrations of proinflammatory cytokines were determined by enzyme immunoassay. Conclusion. The data obtained confirm that this multibiomarker panel is a promising tool for early detection, risk assessment, and the development of individual management strategies for patients with coronary heart disease. Combined assessment of epigenetic, inflammatory, and cardiovisual biomarkers can improve risk stratification and aid in clinical decision-making.